Religious Exclusivity, Harmony and Moderatism amid Populism: A Study of Interreligious Communication in West Sumatra - Roma Ulinnuha (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
The religious moderatism is one of the constructive efforts in a diverse religious society. Plurality of beliefs as a whole part of the social landscape of Indonesian society is not yet fully understood and believed by the religious community. In the era of Populism, moreover in the dimension of religious practice, the case in West Sumatra shows horizontal disagreement or disharmony related to symbols and material aspects of religion such as the establishment of religious ritual places and supporting resource. This article confirms that communication serves vitally in addressing religious exclusivity. Resistance to religious entities is always found, as one of the markers of Populism, so that the symbolic interaction of religious leaders in undermining conflict and violence is indispensable. Religion pays particular attention to a social construct and practice with the main purpose of harmony and moderatism of religion. It serves effectively as a contribution of communicative actions, as conveyed by Jurgen Habermas, through reconciliation among religious people. The values of interaction between religious people are emphazised with the principle of agreement and respect as fellow citizens and human beings.